Algorithm for selecting the location of measurement points in gravity sewerage - Gil, Bożena (Instal, 2021)
Wastewater flow monitoring is increasingly important in the management of the sewer network. Among the measuring devices, the devices that are using indirect methods (i.e. simultaneous measurement of the filling and speed in the sewer) to calculate the flow are becoming increasingly popular. This type of equipment allows for everyday control of the operation of the sewage network without the need to rebuild it to install the measuring devices. In such cases, the choice of the location of the measuring point is at least as important as the choice of a device. There are many publications in the literature that focus on the description of technical conditions for the assembly of measuring devices (e.g. by providing appropriate length of straight channels, maintaining a uniform cross-section and slope, elimination of flow disturbing elements). These are very important technical recommendations. They allow for the proper selection of the measurement point, but only when there are stable hydraulic conditions in the sewerage system, both for dry and rainy weather. In practice, however, when choosing a measurement point, errors are often made by not taking into account temporary phenomena (such as temporary flow disturbances) which appear in the network only under certain conditions. These phenomena can have a significant impact on the overall measurement results. When a measurement point is installed on an existing sewer network, without reconstruction of the sewer, such temporary flow disturbances are highly probable. To detect these disturbances, a hydraulic flow analysis is necessary. This analysis should be carried out on the basis of test measurements. These measurements should be carried out for short periods of time and, once the anomaly has been detected, the analysis extended to include an analysis of the network’s operating conditions over the entire range of flow variations. This serves to determine the probability with which hydraulic conditions, deviating from the stable conditions, will occur. This analysis can be performed on the basis of a hydraulic model made for a fragment of a sewer network. The results of this analysis can be used to: select, another better measurement point, indicate and remove of disturbing factors from the network, introduce corrections to measurement algorithms (taking into account the influence of the anomaly), develop instructions for supervision and maintenance of the measurement point. All these elements are aimed at improving the reliability of sewage flow measurement results in sewage systems.
Keywords: sewage networks; flow measurement; measuring point location; hydraulic analysis; hydraulic model